The Effect of Financial Soundness Level on Premium Growth of Companies Listed in AASI - Andika Rizki Pradana; Sulhani (Journal of Islamic Contemporary Accounting and Business, 2024)
Analyze how the effect of financial health level as measured by liquidity ratio, investment balance ratio with liabilities, investment income ratio, claim expense ratio, tabarru' fund change ratio, and risk-based capital ratio on premium growth of Islamic insurance companies listed in the Indonesian Sharia Insurance Association (AASI) for the period 2018-2022. Quantitative research using panel data regression analysis with SPSS 26 program.There is a significant influence between the variable ratio of investment income on the growth of premiums of Islamic insurance companies indicated by a partial significance test value of 0.044 <0.05 and there is also an influence between the variable ratio of changes in tabarru's funds on the growth of Islamic insurance premiums indicated by a partial significance test value of 0.007 <0.05. Meanwhile, there is no influence between the variables of liquidity ratio, investment balance ratio with liabilities, claim expense ratio, and risk-based capital (RBC) ratio on the growth of premiums of Islamic insurance companies.